Huella de carbono en la actividad productiva de coco de la hacienda Juananu en el sitio Cañaveral-cantón Pedernales - Solórzano Guerrero, Ronaldo Wanderley (2024)
The present research was conducted at the Juananu farm, Cañaveral site, located in Pedernales canton, on the Cojimíes road at km 11.5. The objective was to evaluate the carbon footprint associated with climate change adaptation mechanisms in coconut production. The research employed quantitative and deductive methods, as well as techniques such as observation and interviews. This allowed for the assessment of the current situation of coconut production at the Juananu farm, where activities generating greenhouse gasses (GHGs) were identified, and monthly consumption of fuel, water, and electricity was determined. Subsequently, the carbon footprint was calculated, showing that the total CO2 emissions recorded during August and September 2023 amounted to 39,802.078 kg CO2eq. Finally, a guide of strategies to reduce CO2 emissions in coconut production was proposed, including: replacing low-octane fuels with high-octane alternatives; separating inorganic waste, classifying it, and handing it over to an authorized manager; using coconut husk for the benefit of the crop itself; replacing synthetic agrochemicals with biofertilizers and natural-origin composts; and lastly, saving water and energy through machinery maintenance and efficient use, optimizing irrigation systems, collecting and storing rainwater, and using energy-saving lighting.